Effects of phenological mismatch under warming are modified by community context - Pardikes, Nicholas (Dryad, 2022)
Climate change is altering the relative timing of species interactions by
shifting when species first appear in communities and modifying the
duration organisms spend in each developmental stage. However, community
contexts, such as intraspecific competition and alternative resource
species, can prolong shortened windows of availability and may mitigate
the effects of phenological shifts on species interactions. Using a
combination of laboratory experiments and dynamic simulations, we
quantified how the effects of phenological shifts in Drosophila-parasitoid
interactions differed with concurrent changes in temperature,
intraspecific competition, and the presence of alternative host species.
Our study confirmed that warming shortens the window of host
susceptibility. However, the presence of alternative host species
sustained interaction persistence across a broader range of phenological
shifts than pairwise interactions by increasing the degree of temporal
overlap with suitable development stages between hosts and parasitoids.
Irrespective of phenological shifts, parasitism rates declined under
warming due to reduced parasitoid performance, which limited the ability
of community context to manage temporally mismatched interactions. These
results demonstrate that the ongoing decline in insect diversity may
exacerbate the effects of phenological shifts in ecological communities
under future global warming temperatures.
We experimentally manipulated the timing of host-parasitoid interactions
in current and expected warming temperatures. We did this in high and low
levels of resource competition and in simple and complex communities. We
also used this data to parameterize a multigenerational dynamic model to
investigate the long-term consequences of phenological shifts.
Keywords: FOS: Biological sciences; phenology mismatch; host-parasitoid dynamics